All Days 2010
DOI: 10.2118/138649-ms
|View full text |Cite
|
Sign up to set email alerts
|

Rock Physics Characterization Using Acoustic Velocity Measurements On Late Cretaceous Carbonate Rocks From the Middle East

Abstract: We conducted laboratory measurements of Vp (compressional waves), Vs (shear waves), porosity and permeability on forty nine dry carbonate core plug samples at ambient pressure and temperature. We also, performed an initial lithological description, based on Dunham's carbonate rock classification to fully characterize the samples. The study results were analyzed to search for potential correlations between the different rock properties and lithological characteristics. We used cross plots of porosity-permeabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…A series of studies investigated the relationship between acoustic velocity and permeability and tried to define the factors controlling acoustic velocity and permeability in carbonates [64,[71][72][73][74][75], and found that pore structure, size, connectivity, and distribution are the main factors controlling acoustic velocity and permeability. The majority of these studies have shown an inverse relation between permeability and acoustic velocity, either as direct or indirect relation.…”
Section: Permeability Bioturbation and Compressional Velocitymentioning
confidence: 99%
“…A series of studies investigated the relationship between acoustic velocity and permeability and tried to define the factors controlling acoustic velocity and permeability in carbonates [64,[71][72][73][74][75], and found that pore structure, size, connectivity, and distribution are the main factors controlling acoustic velocity and permeability. The majority of these studies have shown an inverse relation between permeability and acoustic velocity, either as direct or indirect relation.…”
Section: Permeability Bioturbation and Compressional Velocitymentioning
confidence: 99%